INVESTIGATION OF ANTI-INFLAMMATORY ACTIVITY POLYHERBAL FORMULATION (CALOTROPIS GIGANTEA AND GLYCYRRHIZA GLABRA) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Traditional medicine is defined as therapeutic practices that have been in existence, for hundreds of years before the development and spread of modern sciences. This is due to the fact that traditional medicine is the most affordable and accessible health care system available. Ayurveda mentions number of plants for the management of several diseases. Several researchers had given their contributions for finding hidden therapeutic activities of Ayurvedic drugs, but still number of plants need a comprehensive study on them. The present study is focused on the investigation of the potent medicinal herbs such as Calotropis gigantea belongs to family Asclepiadaceae, Glycyrrhiza glabra belongs to family Leguminosae for their anti-inflammatory activity in the form of polyherbal formulation. In carrageenan induced inflammation the polyherbal formulation showed a maximum anti-inflammatory effect at 120 min (71.17%) and progressively increased by 180 min (78.1%). And similarly in formalin induced inflammation the anti-inflammatory effect induced by polyherbal formulation progressively increased and reached a maximum of 72.24% at 180 min. The present investigation concluded that the plants Calotropis gigantea and Glycyrrhiza glabra in the form of polyherbal formulation having anti-inflammatory activity.